Efficient Removal of Micro-Sized Degradable PHBV Microplastics from Wastewater by a Functionalized Magnetic Nano Iron Oxides-Biochar Composite: Performance, Mechanisms, and Material Regeneration - Huaguo Xia; Nini Duan; Beisi Song; Yuan Li; Hongbin Xu; Ying Geng; Xin Wang (Nanomaterials, 2025)
The co-occurrence of the synthesis of a functionalized magnetic nano iron oxides–biochar composite (MFe@BC) via impregnation–thermal pyrolysis and its use to remove micro-sized poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) microplastics from simulated wastewater was demonstrated in this study. The results showed that PHBV removal efficiency correlated positively with MFe@BC dosage, achieving an adsorption capacity of 13.14 mg/g and a removal efficiency of 98.53% at an optimal dosage of 1.5 g/L. Adsorption kinetics fit a pseudo-second-order model (R2 = 0.9999), and the isotherm followed the Langmuir model (R2 = 0.8440), yielding a theoretical maximum capacity of 31.96 mg/g. Characterization indicated chemisorption-driven monolayer adsorption via surface complexation and hydrogen bonding. Magnetic nano-iron transfer from MFe@BC to the PHBV surface imparted magnetic properties to PHBV, enabling synergistic adsorption and magnetic separation. Removal efficiency remained above 95% across pH 4–9 and COD 0–500 mg/L. Regeneration experiments indicated that the MFe@BC showed robust reusability, maintaining >92% PHBV removal efficiency after four adsorption–regeneration cycles. The results of this study may provide a feasible pathway for PHBV microplastic removal from secondary effluent, indicating that MFe@BC prepared in this study can be used for the removal of PHBV microplastics in a wide range of water bodies.